Porosity inversion and determination in gob unconsolidated materials based on acoustic signal response - Shuai-Jing Ren; Le-Xiang-Qian Zhang; Jun Deng; Jin-Rui Wang; Cai-Ping Wang; Yang Xiao; Fu-Ru Kang; Hai-Jian Li; Long-Hui Dou (Fuel, 2026)

Oxygen-vacancy-driven dipole ordering and anion anchoring in BaTiO3 nanofibers for high-performance gel polymer electrolytes in high-voltage lithium metal batteries - Yaoxiang Shan; Cong Kang; Bingkun Zang; Ting Li; Bingjia Lu; Rui Sun; Huiying Qu; Xucai Yin; Yang Ren (Chemical Engineering Journal, 2026)

Hydrogel-encapsulated microalgae-bacteria consortia for resilient saline agriculture - Xiao-Jing Wang; Nan Wu; Xiao Yu; Si-Ming Li; Zi-Rui Yang; Zhi-Hai Zhong; Kang Wang; Hong-Li Cui; Cheng-Gang Ren; Song Qin (World Journal of Microbiology and Biotechnology, 2026)

Exposure to second-generation flame retardants and risk of metabolic diseases: a systematic review and meta-analysis - Li Shi; Wei Du; Xi-Yuan Peng; Juan Miao; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Zhi-Ren Mu; Hong-Lin Chen (Archives of Toxicology, 2026)

Composite hydrogel microspheres modulate intestinal inflammation via releasing HA modified liposomes@4-OI targeting M1 macrophages - Shuanghong Yang; Ze Li; Guiwen Qu; Liting Deng; Liuqing Dou; Sicheng Li; Yitian Teng; Luqiao Huang; Haohui Li; Kang Chen; Jinpeng Zhang; Rui Ma; et al. (Chemical Engineering Journal, 2026)

Automatic Image Co-registration of Carotid Angiography and Intravascular Optical Coherence Tomography Based on Machine Learning Method: A Pilot Feasibility Study - Hui Xu; Jia-Nan Li; Yan Xu; Jun-Ren Ma; Kang Zong; Rui Zhu; Yi-Hui Cao; Peng-Fei Yang; Rui Zhao; Jian-Min Liu (Annals of Biomedical Engineering, 2026)

Enhanced capacitive deionization performance of core-shell FeHCF@NiHCF Prussian blue analogue benefited from interface effect - Zewen Fan; Wannan Wang; Jing Ren; Rui-Peng Ren; Yong-Kang Lv (Journal of Environmental Chemical Engineering, 2025)

Effects of Bacillus licheniformis supplementation on growth performance, intestinal health and oxidative stress in weaning transition male dairy calves - Yulin Ma; Yubin Ma; Shuangming Yang; Yuchen Cheng; Wenyi Ren; Xiaonv Liu; Rui Wang; Yan Kang; Haibo Li; Lili Zhang; Xiaofeng Xu (Animal Feed Science and Technology, 2025)

High internal phase emulsion system for curcumin delivery co-constructed by wheat gluten amyloid fibrils and Lycium barbarum polysaccharide - Ren Li; Rui Kang; Rumeng Li; Sai Cui; Huijuan Zhang (Food Research International, 2025)

Stabilizing zinc anode with multifunctional glycine copper additive - Lang Chen; Yue Tian; Bing-Chen Liu; Bo-Xuan Zhang; Kang-Rui Ren; Zhuo-Yun Song; Pengfei Wang; Zonglin Liu; Qianyu Zhang; Jie Shu; Ting-Feng Yi (Chemical Engineering Journal, 2025)

Impact of Bacillus Licheniformis supplementation on growth performance, health status, and oxidative stress in male dairy calves during the weaning transition period - Yulin Ma; Yubin Ma; Shuangming Yang; Yuchen Cheng; Wenyi Ren; Xiaonv Liu; Rui Wang; Yan Kang; Haibo Li; Lili Zhang; Xiaofeng Xu (Animal Feed Science and Technology, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Construction of wheat gluten amyloid fiber/lutein complex delivery system: Formation mechanism, in vitro bioaccessibility, and photothermal stability - Tiancong Song; Ren Li; Mengmeng Zhang; Rui Kang; Huijuan Zhang; Jing Wang (Food Bioscience, 2025)

Photo-crosslinking modified gelatin-silk fibroin hydrogel for accelerating wound repair of open abdomen - Ye Liu; Sicheng Li; Jinjian Huang; Xuanheng Li; Ze Li; Canwen Chen; Guiwen Qu; Kang Chen; Yitian Teng; Rui Ma; Xiuwen Wu; Jianan Ren (Chemical Engineering Journal, 2024)

A variable weight combination prediction model for climate in a greenhouse based on BiGRU-Attention and LightGBM - Xiaojuan Mao; Ni Ren; Peiyu Dai; Jing Jin; Baojia Wang; Rui Kang; Decui Li (Computers and Electronics in Agriculture, 2024)

Tracing spatial patterns of lacustrine groundwater discharge in a closed inland lake using stable isotopes - Xiaohui Ren; Ruihong Yu; Rui Wang; Jianfang Kang; Xiangwei Li; Pengxuan Zhang; Tingxi Liu (Journal of Environmental Management, 2024)

In situ bioprinting of double network anti-digestive xanthan gum derived hydrogel scaffolds for the treatment of enterocutaneous fistulas - Kang Chen; Jinjian Huang; Ze Li; Jinpeng Zhang; Sicheng Li; Canwen Chen; Ye Liu; Guiwen Qu; Yitian Teng; Rui Ma; Zongan Li; Yungang Jiang; et al. (Carbohydrate Polymers, 2024)

Hcprismatin-14 of Hyriopsis cumingii, a novel matrix protein is crucial for framework recognition and crystal deposition during prismatic layer formation - Can Jin; Yihang Zhang; Kang Cheng; Rui Jiang; Shangning Jiang; Yezhong Shi; Gang Ren; Wen Luo (Frontiers in Marine Science, 2023)
Mollusk shells are characterized by hierarchical aggregation of calcium carbonate and organic matrix, and matrix protein is considered as a key active ingredient to understand shell biomineralization. In this study, a total of 21 proteins, including a novel matrix protein Hcprismatin-14 were identified in the EDTA-soluble matrix of the prismatic layer of the mussel Hyriopsis cumingii by liquid chromatography tandem mass spectrometry (LC-MS/MS). The full length of Hcprismatin-14 cDNA was cloned from the mantle of H. cumingii . Hcprismatin-14 contains a high proportion of Gly, Tyr, Arg and Asp residues, their concentrated distribution forms three structurally characteristic regions: a Gly/Tyr-rich region, a WDD-repeat region and a C-terminal basic tail. Hcprismatin-14 expression was high in mantle edge tissue in a tissue-specific analysis, and during disordered crystal deposition in a saibo transplantation assay. Knocking down Hcprismatin-14 expression with double-stranded RNA induced subgrains deposition inhibition and lost contact with chitinous scaffold. In addition, the WDD-repeat region polypeptide was involved in morphological regulation of calcite and had dose-dependent inhibitory activity against aragonite deposition in vitro . Based on these results, Hcprismatin-14 appears to be a dual-function prismatic-layer matrix protein, responsible for both framework recognition and crystal deposition. These findings contribute to understanding the relationship between the modular structure of matrix protein and their regulation mechanism during shell biomineralization in mollusks.

High density mapping of wheat stripe rust resistance gene QYrXN3517-1BL using QTL mapping, BSE-Seq and candidate gene analysis - Shuo Huang; Yibo Zhang; Hui Ren; Xin Zhang; Rui Yu; Shengjie Liu; Qingdong Zeng; Qilin Wang; Fengping Yuan; Ravi P. Singh; Sridhar Bhavani; Jianhui Wu; et al. (Theoretical and Applied Genetics, 2023)

Interfacial fluoride engineering enabled robust LiF-rich solid electrolyte interphase to reduce active lithium loss in rechargeable lithium battery - Tianqi Jia; Geng Zhong; Sirong Lu; Xiaolong Ren; Yao Lv; Nanrui Li; Rui Yin; Guohuang Kang; Kangning Cai; Feiyu Kang; Yidan Cao (Chemical Engineering Journal, 2023)

Construction of 3D Ni2+-Al3+-LDH/γ-Fe2O3-Cd2+-Ni2+-Fe3+-LDH structures and multistage recycling treatment of dye and fluoride-containing wastewater - Rui Dang; Xiang-Rong Ma; Yun-Peng Zhao; Menjiao Ren; Wei Guo; Yu-Hong Kang; Yong Gao; Shiqing Bi; Wenwen Gao; Hua-Rui Hao; Rui Bai; Yu-Fei Wang; et al. (Chemical Engineering Journal, 2023)

Prehistoric agriculture development in the Yunnan-Guizhou Plateau, southwest China: Archaeobotanical evidence - HaiMing Li; XinXin Zuo; LiHong Kang; LeLe Ren; FengWen Liu; HongGao Liu; NaiMeng Zhang; Rui Min; Xu Liu; GuangHui Dong (Science China Earth Sciences, 2016)

Inoculation of Fe/Mn-oxidizing bacteria enhances Fe/Mn plaque formation and reduces Cd and As accumulation in Rice Plant tissues - Ming Fang Dong; Ren Wei Feng; Rui Gang Wang; Yang Sun; Yong Zhen Ding; Ying Ming Xu; Zhi Lian Fan; Jun Kang Guo (Plant and Soil, 2016)

Burkholderia metalliresistens sp. nov., a multiple metal-resistant and phosphate-solubilising species isolated from heavy metal-polluted soil in Southeast China - Jun Kang Guo; Yong Zhen Ding; Ren Wei Feng; Rui Gang Wang; Ying Ming Xu; Chun Chen; Xiu Li Wei; Wei Min Chen (Antonie van Leeuwenhoek, 2015)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)